Gas in scattering media absorption spectroscopy on small and large scales: Toward the extension of lung spectroscopic monitoring to adults. Issue 3 (10th July 2021) - Lin, Yueyu; Lundin, Patrik; Krite Svanberg, Emilie; Svanberg, Katarina; Svanberg, Sune; Sahlberg, Anna‐Lena
Abstract: Numerous natural materials are porous, contain free gas and are scattering light strongly. Scattering brings about a strong trapping of light and an associated prolonged transit time for photons through a medium. In contrast to the matrix materials, gas enclosures require very narrowband laser radiation for probing. We have in the present study used the gas in scattering media absorption spectroscopy method to study free oxygen in thin (cm) samples utilizing a tunable diode laser, while a pulsed dye laser was employed in corresponding measurements on larger samples, up to the meter scale. Time‐resolved spectroscopy was in both cases used to assess the temporal distribution of the detected photons, mapping the path lengths through the media, which ranged between few centimeters up to 100 m. This study explores the feasibility to extend recent successful monitoring of gases in neonatal infant lungs to the case of larger children or even adults, which could have very important applications, for example, in ventilator setting optimization for severely ill patients, suffering, for example, from SARS‐CoV‐2. The conclusion of our work is that this goal most realistically can be reached by applying intratracheal laser light illumination at the 1 W power level, employing a tapered amplifier, injected with a distributed feedback diode‐laser oscillator output and combined with wavelength‐modulation spectroscopy. Abstract : This study explores the feasibility to extend recent successful monitoring of gases in neonatal infant lungs to the case of larger children or even adults, which could have very important applications, for example, in ventilator setting optimization for severely ill patients, suffering, for example, from SARS‐CoV‐2. This goal most realistically can be reached by applying intratracheal laser light illumination at the 1 W power level, employing a tapered amplifier, injected with a distributed feedback diode‐laser oscillator output and combined with wavelength‐modulation spectroscopy.